POLITISI DAN PEMANFAATAN MEDIA SOSIAL - Sumartono Mulyo Diharjo (Jurnal Komunikasi dan Bisnis, 2019)
It can not be denied, at this time facebook has become a political communication channels in Indonesia. Even facebook has transformed into the strength of the disputed new medium politicians or political communicators in disseminating its existence. Members of house of representatives as actor of political communication has been using or utilizing social media Facebook as a channel of dissemination or information to its constituents.  Based on the fact of the field facebook has helped promote the existence or the existence of a legislative member to the society in the midst of the growing phenomenon of money politics. Through the utilization of facebook use or financial expenditure can be minimized. That is, the facebook are very helpful to promote the presence of members of the legisltatif (both in the period before and after becoming a member of house of representative) to the community, so that the mass media (mainly print) that had become a mainstay in the socialization as replaceable by facebook. Presence of facebook really help a candidate to manage the limitations of funds owned and become a new trend of political communication channel. Tidak dapat dipungkiri, saat ini facebook telah menjadi saluran komunikasi politik di Indonesia. Bahkan facebook telah menjelma menjadi kekuatan media baru yang diperebutkan para politisi atau komunikator politik dalam mensosialisasikan eksistensinya. Anggota legislatif sebagai pelaku komunikasi politik telah menggunakan atau memanfaatkan media sosial Facebook sebagai sarana sosialisasi atau informasi kepada masyarakat.  Berdasarkan fakta lapangan facebook telah banyak membantu mempromosikan keberadaan atau eksistensi seorang anggota legislatif kepada masyarakat di tengah berkembangnya fenomena money politics atau politik uang. Melalui pemanfaatan facebook pengunaan atau pengeluaran keuangan dapat diminimalisasi. Artinya, media facebook sangat membantu mensosialisasikan keberadaan anggota legisltatif (baik pada masa sebelum maupun setelah menjadi anggota legislatif) kepada masyarakat, sehingga media massa (terutama cetak) yang selama ini menjadi andalan dalam sosialisasi seakan tergantikan oleh facebook. Kehadiran facebook sangat membantu seorang kandidat dalam mengelola keterbatasan dana yang dimiliki dan menjadi trend baru saluran komunikasi politik.